2017
DOI: 10.1108/el-01-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of user behaviour on multilingual information retrieval

Abstract: Purpose This paper aims to understand user information behaviours when they perform multilingual information retrieval. It also offers reference for the development of multilingual information retrieval systems and relevant service platforms. Design/methodology/approach The authors designed an experiment on multilingual information retrieval with WorldWideScience, utilized Camtasia studio7 (a screen capturing and recording tool) to record overall operational processes of subjects and collected participants’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In the field of the Cross-Language Information Retrieval (CLIR), Nzomo et al (2016) stated that increasing multilingual information access (MLIA) tools on electronic databases along with proper information literacy training can be very useful for overcoming language barriers. The findings of Si et al (2017) also showed that users preferred their own language for retrieval. Most subjects chose keywords directly from the tasks they were given as a query.…”
Section: Ajim 733mentioning
confidence: 85%
See 2 more Smart Citations
“…In the field of the Cross-Language Information Retrieval (CLIR), Nzomo et al (2016) stated that increasing multilingual information access (MLIA) tools on electronic databases along with proper information literacy training can be very useful for overcoming language barriers. The findings of Si et al (2017) also showed that users preferred their own language for retrieval. Most subjects chose keywords directly from the tasks they were given as a query.…”
Section: Ajim 733mentioning
confidence: 85%
“…These studies have suggested that thesauruses can be a useful resource for selecting queries (Fidel, 1991;Spink, 1994;Brajnik et al, 1995;Efthimiadis, 1996;Sutcliffe et al, 2000;Vakkari, 2000;Shiri et al, 2002Shiri et al, , 2011Shiri et al, , 2010Shiri et al, , 2011Wu, 2010;Chandra and Dwivedi, 2020). The results of the research of R ozsa et al (2015) and Si et al (2017) showed that searchers whose main language was not English turned to English query hoping to find more event results because most of the scientific publications are in English (Peters et al, 2012). In this process, where the question of translation is a major challenge in the various stages of compiling the query (Oard et al, 2008;Nie, 2010;Peters et al, 2012), the use of semantic tools such as ontology can help researchers find important words.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study [26], differences in collaborative information seeking, when compared to the individual's model of the ISP, were identified specifically in the cognitive and affective associated with the part of the process involving the information searcher making relevance judgements. Interestingly, the findings from studies that have likewise focused on behavioural analysis of non-native language speakers information retrieval have suggested the need for subject-specific lexis [30], the importance of online reading abilities [4,19], and the preference for 'their own language for retrieval' [27]. The findings of these studies, as such, appear to suggest that to enable search, focus must be placed on the language used in the activities involved in accomplishing the search process.…”
Section: Literature Reviewmentioning
confidence: 99%